Análise do transcriptoma de córtex cerebral da prole de camundongos infectados por Zika virus - Letícia Maria Soares Azevedo (2022)
Zika virus (ZIKV) is an arbovirus that belongs to the Flaviviridae family and its symptoms are associated with clinical signs as acute fever, headache, myalgia, maculopapular rash, sore throat and edema in the lower limbs. Neurological complications associated with this virus infection are also observed, as Guillain-Barré Syndrome (GBS) and microcephaly in newborns, further fetal anomalies, in which is defined as Congenital Zika Syndrome (CZS). But the consequences of infection in adulthood are still being investigated, especially in the context of co-circulation of other flaviviruses, which can cause tthe phenomenon of ADE (Antibody-Dependent Enhancement). Therefore, the objective of this work was, through transcriptome analysis, to evaluate the expression of differential genes in offspring born from mothers infected with ZIKV, in the presence or absence of anti-flavivirus antibodies. For this, pregnant female mice were inoculated with 1x106 PFU/animal of ZIKV intraperitoneally on embryonic day 5.5, in the presence or absence of 4G2. After 12 weeks of offspring birth, the puppies were euthanized and the cerebral cortex was collected for transcriptome analysis. Six samples from each group were sequenced using the HiSeq 2500 equipment (Illumina, San Diego, CA, USA). The transcriptome analysis followed the steps: quality control, alignment, summarization, quantification, normalization, differential expression analysis and analysis of set gene enrichment. The animal groups were compared to each other, which are PBS, ZIKV and 4G2+ZIKV. Few differentially expressed genes were observed when comparing PBS and ZIKV, most of which were suppressed and are mainly related to cell cycle and morphogenesis. On the other hand, when comparing ZIKV and 4G2+ZIKV, a large amount of genes activated was observed, referring to the immune response and production of cytokines and inflammatory mediators, which altered important pathways in the host organism's attempt to contain the infection. The repression of cellular and morphological processes was also observed, which corroborate the pathogenesis of ZIKV, especially in the development of the nervous system. Neurological alterations were better observed in the analysis of alternative splicing, which revealed transcripts originating from genes different from those differentially expressed, which mainly change neurological development in the group with the presence of 4G2. Therefore, the transcriptome analysis elucidates the severity of co-infections in the context of ZIKV, by observing more accentuated genetic and metabolic alterations in the presence of 4G2, which contribute to a more severe phenotype and complications in the individual's adult phase.